ANALISIS STRATEGI DIFERENSIASI PRODUK DAN PERSONALIA TERHADAP KEPUASAN NASABAH BANK PERKREDITAN RAKYAT (BPR) DI WILAYAH KABUPATEN MADIUN - Wihara, Dhiyan Septa; Haqqi, Rilla Izzatul (Universitas Nusantara PGRI Kediri, 2017)
This research have a purpose (1) to analyze the influence of Diferetiation product strategy depend on customers satisfaction BPR “Rural Bank” in madiun regency (2) to analyze the influence of Diferentation employee strategy depend on customers satisfaction BPR “Rural Bank” in madiun regency(3) to analyze the influence of diferentiation product strategy and diferentiation employee strategy depend on the customers satisfaction BPR”Rural Bank” in Madiun regency.(4)to analyze dominant variabel most influence depend on customers satisfaction BPR “Rural bank” in madiun regency. The kind of this research is explanatory research with quantitative approach. The sample of this research is customers of BPR”Rural Bank” in Madiun regency number in 100 customers with sampling technique using Quota sampling. The data collected using quistionary. The data that the researcher get to be analyze using multiple regresion analyze, Simultaneous (F-test) and Partial(t-test). The result on the research show that the diferentiation product strategy and diferentiation employee strategy in simultaneous give significant influence depend on customers satisfaction BPR”Rural Bank” in madiun regency with significant score 0,000 (p<0.05). This score show that the diferentiation product strategy in partial does not giving significant influence depend on the customers satisfaction BPR”Rural bank” in madiun regency. The t-test show the score 0,286 on the other hand. At the same time diferentiation employee strategy in partial giving significant influence depend on customers satisfaction BPR”Rural bank” in Madiun city, show the score with score significant t-test 0,001.Diferentiation employee strategy is dominant variabel to influence customers satisfaction BPR “Rural bank” in madiun regency.